Normal oil body formation in Marchantia polymorpha requires functional coat protein complex I proteins - Kanazawa, Takehiko; Nishihama, Ryuichi; Ueda, Takashi (Frontiers in Plant Science, 2022)
Eukaryotic cells possess endomembrane organelles equipped with specific sets of proteins, lipids, and polysaccharides that are fundamental for realizing each organelle’s specific function and shape. A tightly regulated membrane trafficking system mediates the transportation and localization of these substances. Generally, the secretory/exocytic pathway is responsible for transporting cargo to the plasma membrane and/or the extracellular space. However, in the case of oil body cells in the liverwort Marchantia polymorpha, the oil body, a liverwort-unique organelle, is thought to be formed by secretory vesicle fusion through redirection of the secretory pathway inside the cell. Although their formation mechanism remains largely unclear, oil bodies exhibit a complex and bumpy surface structure. In this study, we isolated a mutant with spherical oil bodies through visible screening of mutants with abnormally shaped oil bodies. This mutant harbored a mutation in a coat protein complex I (COPI) subunit MpSEC28, and a similar effect on oil body morphology was also detected in knockdown mutants of other COPI subunits. Fluorescently tagged MpSEC28 was localized to the periphery of the Golgi apparatus together with other subunits, suggesting that it is involved in retrograde transport from and/or in the Golgi apparatus as a component of the COPI coat. The Mpsec28 mutants also exhibited weakened stiffness of the thalli, suggesting impaired cell-cell adhesion and cell wall integrity. These findings suggest that the mechanism of cell wall biosynthesis is also involved in shaping the oil body in M. polymorpha, supporting the redirection of the secretory pathway into the cell during oil body formation.